2016
DOI: 10.1021/acssensors.6b00216
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Responsive 19F MRI Contrast Agents for the Detection of Cancer Cells

Abstract: Stimuli-responsive contrast agents (CAs) show great promise for the early detection and understanding of cancer. In particular, CAs that respond to ion content may allow monitoring of both the development of cancer and the efficacy of novel therapies. Understanding the responsive behaviour of stimuli-responsive CAs in different ionic environments requires development of more advanced characterization methods. Here we report a high-resolution NMR and molecular dynamics (MD) study of conformational changes of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…Fluorinated substrates are well established drugs and diagnostic pharmaceuticals in many medical applications, such as the antidepressant fluoxetine or the inhalational anesthetic desflurane ,. Even their potential as contrast agents has already been demonstrated . Due to the importance of these substrates in medicine, studies on the pharmacokinetics, metabolism, interaction with other biomolecules, or localization of the site of pharmacological action increasingly use MRS and MRI techniques because these enable non‐invasive three‐dimensional and time‐resolved detection of structures and dynamics of NMR‐detectable substrates, proteins, and biological tissue.…”
Section: Figurementioning
confidence: 99%
“…Fluorinated substrates are well established drugs and diagnostic pharmaceuticals in many medical applications, such as the antidepressant fluoxetine or the inhalational anesthetic desflurane ,. Even their potential as contrast agents has already been demonstrated . Due to the importance of these substrates in medicine, studies on the pharmacokinetics, metabolism, interaction with other biomolecules, or localization of the site of pharmacological action increasingly use MRS and MRI techniques because these enable non‐invasive three‐dimensional and time‐resolved detection of structures and dynamics of NMR‐detectable substrates, proteins, and biological tissue.…”
Section: Figurementioning
confidence: 99%
“…Hao et al investigated the LCST behavior of copolymers between polycaprolactone and OEGMAs and their interactions with doxorubicin (DOX) by both experimental and coarse‐grained MD methods . Zhang et al reported the conformational changes of the copolymers between OEGMA and 2,2,2‐trifluoroethyl acrylate [poly(OEGMA‐ co ‐TFEA)] during the phase transition by means of NMR and MD techniques . To the best of our knowledge, there is not any study only on OEGMA‐based homopolymers yet that was carried out by MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of MeI‐PDMAPMA was evaluated using 3T3 fibroblast cells through a 3‐(4,5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium inner salt (MTS) assay. The procedure was based on a protocol previously reported . Briefly, 3T3 fibroblast cells were cultured in DMEM with 10% fetal bovine serum and 1% antibiotic–antimycotic, incubated at 37 °C for 24 h with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%